Grossly Polluting Industries and Their Effect on Water Resources in India - Arif Z.; Sethy N.K.; Swati; Mishra P.K.; Verma B. (My University, 2025)
Industrialization is considered as the pillar of economic development and human welfare in India. Since the previous decade, industrial development has greatly affected water resources like rivers, lakes, groundwater, and so on. This is mainly due to the increase in the percentage of grossly polluting industries (GPIs) such as textiles, tannery, distillery, and drug industries. Since 2011, the number of GPIs increased from 1162â€‰units over 22 states/union territories (UTs) to 2743â€‰units over 36 states/UTs as per the Central Pollution Control Board (CPCB) report, of which about 84% of the GPIs are located in four states, viz. Uttar Pradesh (1218), Haryana (660), Andhra Pradesh (198), and Gujarat (191). According to the National Mission for Clean Ganga (NMCG), the wastewater generated by GPIs is 45% of total water consumption. This is mostly due to small-scale industries having a lack of effluent treatment plants (ETPs). These industries produce major pollutants like Cr from tanneries, organic pollutants from distilleries, dyes from textiles, and other toxic chemicals from drug and hazardous chemical industries, which affect both surface and groundwater resources. This has an adverse effect on aquatic ecosystems and human health both directly and indirectly. There are many initiatives and measures taken by central government like national water policies, revised effluent standards, establishing more common effluent treatment plants (CETPs), adopting projects like zero liquid discharge (ZLD) (reuse and recycling of entire industrial wastewater), and so on. Proper management and monitoring of these measures and policies would help in reducing surface and groundwater pollution. Hence, this chapter is focused on GPIs and their effect on water resources and the management of their discharging effluents. © 2021 John Wiley & Sons Ltd. All rights reserved.